ROMANIAN-GERMAN INTERFERENCES DURING CONSTANTIN BRÂNCOVEANU’S REIGN / INTERFERENȚE ROMÂNO-GERMANE ÎN TIMPUL DOMNIEI LUI CONSTANTIN BRÂNCOVEANU (1688-1714) - LEB, Ioan-Vasile (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2015)
It is well known that Constantin Brâncoveanu’s reign represented an apogee in the development of Ţara Românească, having at the same time influences upon the other Romanian principalities. One of the most interesting chapters is the links with different German cities, among which we can mention Halle too. In the following research we are going to refer to a few moments of the Romanian history relations with the University of this town.